Biomechanical analysis of different K-wire configurations in percutaneous fixation of 2-part proximal humerus fractures - Mohd Azfan Che Yusoff @ Mohd Affandi (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
Proximal humerus fractures account for 5% of all fractures and it is most common in the elderly population above 60 years of age. Closed reduction and percutaneous pinning is a recognized method in the treatment of 2-part proximal humerus fractures. However, the most stable configurations of wires has not been established. The purpose of this study is to determine the most stable configuration of K-wire in the percutaneous fixation of 2-part proximal humerus fractures. This is a biomechanical study using 27 models of synthetic humeri. Transverse osteotomy was done at the surgical neck of humerus and the fracture was fixed using different sizes, types and configuration of wires. The models were tested using torsion testing machine to assess the stiffness of the constructs. Models with four ascending parallel pins only were found to be the least stiff. No significant results obtained by comparing different sizes and types of K-wires. From our results, we conclude that addition of two wires from the greater tuberosity will improve the stability of the fixation.